A new strategy for fabrication of unique heterostructured titanium laminates and visually tracking their synchronous evolution of strain partitions versus microstructure. (30th April 2022) - Ding, Hao; Cui, Xiping; Wang, Zhiqi; Zhao, Tao; Wang, Yuchen; Zhang, Yuanyuan; Chen, Hongtao; Huang, Lujun; Geng, Lin; Chen, Junfeng
Highlights: A new strategy for producing Ti laminates with gradient structure (GS) and heterogeneous lamella structure (HLS) is proposed. Strain partitions versus microstructure evolution is visualized synchronously using ultrahigh-resolution SEM-DIC combined with EBSD. GS/HLS Ti exhibited a superior combination of strength and ductility, which is attributed to HDI stress strengthening and HDI hardening. Abstract: Heterostructured (HS) material with extraordinary mechanical properties has been regarded as one of the most promising structural materials. Here, we reported a new strategy for preparing heterostructured pure titanium laminates that possess a good combination of strength and ductility by combining gradient structure (GS) and heterogeneous lamella structure (HLS). The deformation characteristic versus microstructure evolution of GS/HLS titanium laminates, namely the strain partitions between different-sized grains (480–25 μm) was visualized using a scanning electron microscope (SEM) equipped with electron backscattered diffraction (EBSD) mode combined with the digital image correlation (SEM-DIC) with an ultrahigh spatial resolution for the first time. As a result, the hetero-deformation of unique GS/HLS structure by the characteristic of strain partitions could be accurately captured. While the hetero-deformation could result in the hetero-deformation induced (HDI) stress strengthening and HDI hardening, which were regarded as the key reason that the resulting GS/HLS Ti laminates showed a superior combination of strength and ductility. This could promote a more in-depth understanding of the strengthening-toughening mechanism of heterostructured material. Graphical abstract: Image, graphical abstract